Brucella suis ΔmapB outer membrane vesicles as an acellular vaccine against systemic and mucosal B. suis infection - González, Florencia Muñoz; Bialer, Magali G.; Cerutti, Maria L.; Estein, Silvia M.; Ramis, Lila Y.; Baldi, Pablo C.; Zorreguieta, Ángeles; Ferrero, Mariana C. (Frontiers in Immunology, 2025)
IntroductionSwine brucellosis, caused by Brucella suis, is a worldwide infectious zoonotic disease. Currently, there are no available human or porcine vaccines to protect against B. suis infection, which is primarily acquired through the mucosa. We recently described B. suis MapB, the homologous protein of TamB, the inner membrane component of the TAM system. Our findings indicate that MapB is involved in bacterial cell envelope homeostasis. In this study, we characterize the outer membrane vesicles (OMVs) of B. suis 1330 (wt) and those of B. suis ΔmapB (ΔmapB) mutant strain and evaluate their vaccine potential in mice.MethodsOMVs were isolated using the ultracentrifugation method and characterized through electron microscopy, Dynamic Light Scattering, SDS-PAGE and proteomics. Immunogenicity was assessed by intramuscular immunization of mice with wt OMVs or ΔmapB OMVs, followed by the measurement of antigen-specific antibody levels and functional assays to evaluate the protective capacity of the antibodies. Cellular immunity was assessed by characterizing cytokine secretion through ELISA after in vitro stimulation of spleen cells with heat-killed B. suis. To determine the level of protection conferred by immunization, mice were challenged with virulent B. suis via intraperitoneal or intratracheal routes, and the bacterial load was quantified post-challenge.ResultsDynamic Light Scattering of the OMVs from both strains revealed the presence of spherical structures of 90-130 nm. Proteomic analysis identified 94 and 95 proteins in the wt and ΔmapB OMVs, respectively, including several known Brucella immunogens. Both OMVs showed immunoreactivity with sera from Brucella-infected pigs. Intramuscular immunization of mice with both OMVs induced antigen-specific IgG in serum, with the ΔmapB OMVs group showing higher titers compared to the wt OMVs group. Serum antibodies from both OMVs groups reduced B. suis adherence and invasion of lung epithelial cells and enhanced its phagocytosis by macrophages. Upon in vitro antigen stimulation, spleen cells from mice immunized with ΔmapB OMVs secreted higher levels of interleukin-17 and especially gamma interferon compared to cells from mice immunized with wt OMVs, suggesting the induction of a stronger T helper 1 response in the ΔmapB OMVs group. While immunization with both wt and ΔmapB OMVs achieved the same level of protection following intratracheal infection with B. suis (p<0.01), immunization with ΔmapB OMVs provided higher levels of protection against intraperitoneal infection.DiscussionOverall, these results demonstrate that the B. suis ΔmapB OMVs are immunogenic and capable of inducing both cellular and humoral immune responses that protect against mucosal and systemic B. suis challenges.